UGT1A1 (TA)n genotype is not the major risk factor of cholelithiasis in sickle cell disease children. (9th January 2017) - Joly, Philippe; Renoux, Céline; Lacan, Philippe; Bertrand, Yves; Cannas, Giovanna; Garnier, Nathalie; Cuzzubbo, Daniella; Kebaïli, Kamila; Renard, Cécile; Gauthier, Alexandra; Pialoux, Vincent; Martin, Cyril; et al.
Abstract: Objectives: Because of the increased hemolytic rate, a significant proportion of patients with sickle cell disease (SCD) are prone to develop cholelithiasis. The present study investigated the role of several genetic factors ( UGT1A1 promoter (TA)n repeat polymorphism, alpha‐globin status), hematological parameters, clinical severity, and hydroxyurea (HU) therapy on the occurrence of cholelithiasis in SCD. Methods: One hundred and fifty‐eight children (2–18 yr old) regularly followed at the University Hospital of Lyon (France) were included. A multivariate Cox model was used to test the associations between cholelithiasis and the different parameters analyzed. Results: We confirmed that alpha‐thalassemia and low basal reticulocyte (RET) count were independent protective factors for cholelithiasis while 7/7, 8/8 and 7/8 UGT1A1 (TA)n genotypes were independent predisposing factors for this complication. We also showed for the first time that HU treatment decreased the risk for cholelithiasis while frequent vaso‐occlusive crises and acute chest syndrome events increased that risk. Conclusions: Our findings demonstrate that UGT1A1 (TA)n polymorphism is not the only factor triggering gallstone formation in SCD. Cholelithiasis is also modulated by RET count, the number of deleted alpha‐genes, HU therapy and the frequency of vaso‐occlusive events.